Inovasi Transportasi Modern: Pemanfaatan Medan Elektromagnetik pada Kereta Maglev dan Kendaraan Listrik - Fiana Fiana; Rafika Desfiana; Muhammad Rifki Arrosyid; Muhammad Rosyid Ridho; Diyajeng Luluk Karlina (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The introduction of electromagnetic devices into modern transportation has revolutionized mobility and enabled more rapid, efficient, and reliable solutions. This study examines the use of electromagnetic devices in Maglev and listrik (EV) keretas. Utilizing magnetic levitasi, EV uses electromagnetic principles to propel its hemat energy, whereas Maglev achieves high-speed transportation with low force. This study identifies key technologies, their benefits, and challenges in implementing the system in question. It also examines the system's global impact on energy consumption and environmental degradation. All of this indicates that more extensive innovation and investment in electromagnetic transportation can speed up transitions to ramah lingkungan mobility.